Erkendelsens former - Klausen, Søren Harnow (Slagmark - Tidsskrift for idéhistorie, 2018)
This article explores various ways to distinguish different forms of knowledge. Such an investigation has an obvious practical relevance in light of the current popularity of the concept of knowledge in public discussions about education, business and politics. It is of particular importance to distinguish different “formats” of knowledge, like propositional knowledge, knowledge-how, phenomenal knowledge etc. The received distinctions in this field turn out to be insufficiently precise, and there is a problematic tendency to equate forms of knowledge which are not necessarily identical, e.g. practical knowledge, tacit knowledge and knowledge-how. The standard notions of reflexive knowledge are also in need of further clarification.